Methodology Of Developing Communicative Skills In Future Pedagogues Based On Modern Approaches (In The Case Of Non-Philology Courses) - Saodat Sharipovna Zuparova (Euro Asian Journal Publishing, 2024)
In this article, the issues of communicative competence, the development of professional competence of future teachers, the unity of the three interrelated communicative, interactive and perceptual components in communication, the teacher's professional communicative competence, communicative self-improvement, higher pedagogy training sessions.
Keywords: communicative competence; future teacher; communication